Current status of HPV vaccination - recommendation and introduction in European countries - Martyna Śliwińska; Agata Wiklińska; Julia Szydlik; Katarzyna Wójtowicz (Nicolaus Copernicus University in Toruń, 2024)
Introduction and aim of study: HPV infection is estimated to underlie 5.2% of all cancers. These can affect the cervix, vagina, vulva, anus, penis and head and neck. The main aim of this systematic review was to assess the current knowledge about primary prevention of HPV infection and compare the vaccination data between European countries. Materials and methods: The authors based this review paper on an extensive analysis of scientific articles published in PubMed, Science Direct, UpToDate, Springer, Cochrane and Google Scholar, vaccine reports from 2021 and later years, healthcare-oriented media reports and government information pages. Results: Currently, one of the most effective methods of dealing with HPV-dependent cancers is primary prevention. It is estimated that vaccination can prevent up to 70% of cases of cervical cancer, and with the 9-valent vaccine, this rate can increase to 90%. There are currently 3 types of vaccines available on the market: 2-, 4- and 9-valent. A 2- or 3-dose vaccination schedule can be followed depending on the age of the patient. The main target group of vaccination are children between the ages of 9 and 14. However, adults up to the age of 45 may still gain some benefits from the injection. A 1-dose regimen is under examination in order to increase vaccination rates in regions with the highest incidence of HPV-associated cancers. Due to major differences in vaccination programs and monitoring, it is difficult to compare vaccination coverage in European countries. Conclusion: The HPV vaccine is a very effective method of primary prevention. It is crucial to improve the vaccination rates in European countries, including Poland, in order to lower the incidence of HPV-dependent cancers.